Study of incidence and severity of menopausal symptoms in women of sub Himalayan region, using the Greene Climacteric Scale - Syal, Geetika; Mohindroo, Neha; Rana, Anshul; Mittal, Rita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Identifying and measuring menopausal symptoms using Greene Climacteric Scale and calculating the mean age at menopause to find out the frequency of the menopausal symptoms so that can be used for better perimenapausal and menopausal care to females. Methods: A cross-sectional study was conducted in a tertiary care center in northern India. All menopausal women in gynaecology outpatient department were enrolled in study, over six months from May 2019 to October 2019. A total of 206 women fulfilled the inclusion criteria and were interviewed using the 21 points Greene Climateric Scale (GCS) Questionnaire. Analysis was done using SPSS 20 Windows software. Descriptive statistics included computation of percentages, means and standard deviations. Level of significance was set at P≤0.05. Results: The mean age of menopause was 47.9±3.42 years. About 90.3% of the menopausal women studied belonged to the rural population. The most frequently perceived symptoms by females were muscle joint pain (100%), vaginal dryness and pruritus vulvae (84%), lower abdominal pain (79.6%), hot flushes (50.5%).The most frequently reported symptoms as per the GCS were muscle and joint pains, loss of interest in sex, headaches, feeling tired or lacking in energy, difficulty in concentrating, attacks of anxiety, difficulty in sleeping and hot flushes. The mean total score was 17.61. Conclusions: Menopausal symptoms were common in this study group but women seeking help for the same was less. Therefore menopause clinics and care programmes need to be developed and strengthened to promote better health and higher quality of life in menopausal women.